Optimization of Cancer Treatment: A Control Theory Approach - Mishra, Utpal (Biology, Engineering, Medicine and Science Reports)
In medical diagnostics and treatment, precise administration and monitoring are essential, especially in cancer therapy, where personalized drug dosage becomes critical due to varying patient responses. Human demographics exhibit diverse reactions to drug administration, necessitating individualized treatment regimens for cancer patients. The effects of drugs on cancer cells vary based on dosage, highlighting the need for a mathematical framework to model drug intake, absorption in the gastrointestinal tract, and eventual circulation in the bloodstream. For physicians, initial drug dosing and administration schedules-typically spanning a week-are observed before adjustment. This study mirrors this practical approach by proposing an optimal control therapy for cancer treatment, explicitly using chemotherapy. Through Pharmacokinetics (PK) modelling, one can explore dose optimization strategies to provide patient-specific, optimal drug regimens tailored to individual cancer patients. The research emphasizes the critical role of prior knowledge and control therapy in enhancing treatment outcomes.
Keywords: Oncology; Chemotherapy; Clinical care; Optimal therapy; Personalised medicine